Property rights of Muslim women through inheritance: a brief outlook - Mohd Salim, Wan Noraini; Halim, Akmal Hidayah (ISTAC-IIUM Publications, 2020)
The fact that a woman is biologically different from a man should not differentiate her in respects of her legal rights, including the right to inherit property. However, some claim that women are discriminated against as far as inheritance is concerned and women in Malaysia are not excluded from this discrimination. The preference of men over women in inheritance continues to be debated and disputed especially by the women themselves. Hence, this chapter provides a cursory look into this unsettled issue from both legal and social recognition of women's rights to inherit the deceased's estates. It also briefly considers the extent of inheritance rights given to women in Malaysia by religion or custom and see whether they are adequately protected by statutory provisions. Reference to the position of women in Islam and selected Arab countries in this regard is briefly made. This is due to the common historical background of the legal system in those Arab countries and that of Malaysia as far as Muslim women's inheritance is concerned.